Kajian Penambahan Konsentrasi CMC Terhadap Mutu Jelly Drink Pala (Myristica fragrans Houtt) - Rumalean, Amirudin; Tetelepta, Gilian; Palijama, Syane (Jurnal Agrosilvopasture-Tech, 2024)
This aims of this research was to determine the best nutmeg jelly drink with the addition of CMC concentration based on chemical and organoleptic properties. This research was designed using a single factor Completely Randomized Design with five levels of treatment with the addition of CMC concentration, namely 1.5 %, 2 %, 2.5 %, and 3 %. The research results with the addition of 1.5 % CMC concentration were the best treatment in making nutmeg jelly drink with chemical characteristics, namely pH of 4.0, total acid of 0.98 %, and total dissolved solids of 27 °Brix. Based on the hedonic properties, it is liked by panelists in term of taste, texture, suction power, and overall, and produces a jelly drink that tastes nutmeg, chewy, and easy to suck.